The Influence of Islamic Business Ethics on the Service of Slaughtered Chicken Traders - Wazin Wazin; Aan Ansori; Juria Mumtajah; Muhammad Sirajuddin Qahtan Hamdan (el-Jizya: Jurnal Ekonomi Islam, 2023)
Islamic business ethics is a set of good, bad, right, and wrong values ​​in the business world based on morality. Business in Islam becomes an important element in trade. In this case, traders are those who carry out trading activities as a daily job, generally providing goods that are then resold. As a trader or provider of goods or services, the community needs a pleasant and reassuring buyer. This can be achieved with ethics, of course, it will be more important if the rules in business can apply Islamic ethics in accordance with syar'i teachings. The purpose of this study is to find out and analyze how the influence of Islamic business ethics on the service of slaughtered chicken traders in the Bojonggede Traditional Market. And this study uses quantitative research methods using primary data. The results of this study obtained the value of tcount of 12,380 ttable of 2.00030. Based on this value, the value of tcount > ttable which means rejecting H0 and receiving H1, clearly it can be interpreted that Islamic business ethics affect the service of slaughtered chicken traders at the Bojonggede Traditional Market. Based on R2 shown in the table, it is obtained that the magnitude of Islamic business ethics' influence on Slaughtered traders' service at the Bogor Bojonggede Traditional Market is 72.5%. While the remaining 27.5% is influenced by other factors outside the variables examined in this study.